DINAMIKA KOMUNIKASI KEPALA DESA DENGAN MASYARAKAT DALAM MEMBANGUN SOLIDARITAS SOSIAL MASYARAKATDISUMENEP - Mahfud Ali; Yohandi (Maddah : Jurnal Komunikasi dan Konseling Islam, 2024)
Relationships between humans continue to be sustainable because of communication. Communication is used as a tool to fulfill life's needs. One of them is the communication of government officials in interacting with the public. In this case it is the villa ge head. Village head communication with the community is very important in increasing social solidarity, whether communicating linearly or exchanging ideas (circularly). So that it makes people feel comfortable when communicating with government officials . This is the method used by the Head of Kropoh Village, Sumenep, to interact with his residents. By using linear and circular communication, it can produce good effects and feedback on society. The discussion of this research is about the village head's c ommunication patterns with the community in building social solidarity in the Kropoh Ra'as Village community, Sumenep and the effectiveness of the village head's communication with the community in building social solidarity in the Kropoh Ra'as Village com munity, Sumenep. Qualitative research is used as the main design in research with information sources on village heads' communication with the community in building social solidarity. This type of research is field research and is descriptive in nature and the research data sources are collected through observation, interviews and documentation. The results of this research show that the communication pattern used by the Head of Kropoh Village in communicating with the community is very good and can foster social solidarity by strengthening the sense of mutual cooperation among the community so that they can establish good cooperation in keeping in touch with each other among residents.